2017
DOI: 10.1111/cote.12292
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application to cotton of a polymeric black colorant prepared by grafting of reactive dyes to polyvinylamine

Abstract: A novel polymeric black dye was synthesised by grafting yellow, orange, red, and blue reactive dyes onto polyvinylamine. Such a polymeric black dye takes the onus away from dyers to worry about the compatibility of individual dyes. The polymeric black dye was characterised by Fourier transform infrared, ultraviolet‐visible, and nuclear magnetic resonance spectroscopy. The absorption of the polymeric black dye in aqueous solution was nearly constant across the wavelength range 400–700 nm. Compared with a black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The structures of the synthesised dyes were characterised by TLC, as well as UV‐Vis (Figure S1) and FT‐IR spectroscopy (Figure S2), which confirmed that the reactive dyes had been successfully grafted onto PVAm. The degrees of substitution were determined using the polyvinylamine dye calibration curve (assuming that extinction coefficients of the chromophores before and after grafting will be the same), and a TLC densitometer was used to determine the reactivity of the reactive dyes quantitatively and provide an accurate measurement of the unreacted reactive dyes to calculate the molar ratio of the reacted dyes to the PVAm, which revealed degrees of substitution of 32.4%, 26.5% and 27.4% for polyvinylamine dyes 2a , 2b and 2c , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of the synthesised dyes were characterised by TLC, as well as UV‐Vis (Figure S1) and FT‐IR spectroscopy (Figure S2), which confirmed that the reactive dyes had been successfully grafted onto PVAm. The degrees of substitution were determined using the polyvinylamine dye calibration curve (assuming that extinction coefficients of the chromophores before and after grafting will be the same), and a TLC densitometer was used to determine the reactivity of the reactive dyes quantitatively and provide an accurate measurement of the unreacted reactive dyes to calculate the molar ratio of the reacted dyes to the PVAm, which revealed degrees of substitution of 32.4%, 26.5% and 27.4% for polyvinylamine dyes 2a , 2b and 2c , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These dyes have been applied in various fields, such as textiles, biology, photoelectric materials, among others . They are synthesised by bonding dye chromophores to the main or side chains of polymers through chemical reactions or the diazo couplings of polymeric intermediates …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Polymer dyes can modulate their properties by changing the structures of polymers and chromophores according to the application performance requirements. They may be used as water-soluble polymer dyes that achieve coloration of fibres in aqueous solution [9][10][11][12] and improve the adsorption capacity of dyes on fibres due to the adhesion of polymers, thus improving their dyeing ability and fastness. In particular, the fixation can be significantly improved; this is because the multi-functionality of reactive groups on the dye molecules leads to outstanding fixation efficiencies when reactive dyeing cotton.…”
Section: Introductionmentioning
confidence: 99%
“…1719 Our research group has developed various polyamine dyes by incorporating different chromophores on polyallylamine, polyethylene polyamine or polyvinylamine (PVAm). 2022 They can be prepared by using polyamine macromolecules as the backbones and halogenated aromatic compounds or reactive dyes as the chromophores. Tang et al.…”
mentioning
confidence: 99%
“…[17][18][19] Our research group has developed various polyamine dyes by incorporating different chromophores on polyallylamine, polyethylene polyamine or polyvinylamine (PVAm). [20][21][22] They can be prepared by using polyamine macromolecules as the backbones and halogenated aromatic compounds or reactive dyes as the chromophores. Tang et al 23 invented a water-soluble polymeric dye based on polyallylamine and 2,4-dinitrochlorobenzene, which was evaluated in the dyeing of cotton and silk, and the fixation could reach 99% by the use of a crosslinking agent.…”
mentioning
confidence: 99%